2017
DOI: 10.1016/j.npep.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of CXCL10/CXCR3 signaling in the development of morphine tolerance in periaqueductal gray

Abstract: Tolerance to morphine antinociception hinders its long-term use in clinical practice. Interaction between neuron and microglia has been proved to play critical role in the mechanism of morphine tolerance, while CXCL10/CXCR3 signaling has been implicated in neuron-glia signaling and morphine analgesia. This study aims to investigate whether CXCL10/CXCR3 signaling in periaqueductal gray (PAG) contributes to the development of morphine tolerance by modulating neuron-microglia interaction. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…CXCR3 is expressed constitutively on neurons and neuronal processes in the brain (Xia et al, 2000;Wang et al, 2017;Piotrowska et al, 2018). Here, we found a similar pattern of expression of the receptor.…”
Section: Discussionsupporting
confidence: 77%
“…CXCR3 is expressed constitutively on neurons and neuronal processes in the brain (Xia et al, 2000;Wang et al, 2017;Piotrowska et al, 2018). Here, we found a similar pattern of expression of the receptor.…”
Section: Discussionsupporting
confidence: 77%
“…Our previous studies have demonstrated the important role and complexity of neuron-glia interaction in the mechanism of morphine tolerance ( Peng et al, 2017 ; Wang et al, 2017 ). In the present study, expressions of IRE1 and XBP1 were found to be increased mainly in neurons and astrocytes in spinal dorsal horn, while ATF6 expression was increased mainly in spinal neurons in morphine-tolerant rats.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of morphine always lead to the drug tolerance, and patients may need higher doses of drug to achieve comparable pain relief ( King et al, 2005 ; Williams et al, 2013 ). Considerable advance has been made in the mechanisms underlying morphine tolerance, including desensitization and internalization of opioid receptor ( Narita et al, 2006 ; Martini and Whistler, 2007 ), heterodimers of G protein-coupled receptors ( Pasternak and Pan, 2011 ; Szentirmay et al, 2013 ), involvement of chemokines ( Ye et al, 2014 ; Guo and Gao, 2015 ; Guo et al, 2017 ; Wang et al, 2017 ), etc. However, detailed mechanisms are still far from clear and few strategies are available for the management of morphine tolerance for now.…”
Section: Introductionmentioning
confidence: 99%
“…CXCL10/CXCR3 system has been reported to be the key molecules in enhancing the BBB permeability by rabies virus infection . In addition, CXCL10 might also be secreted into the inside of the brain, and CXCR3 is expressed in neurons . Therefore, TLR3/IFN‐β/CXCL10 and TLR3/IFN‐β/RIG‐I or MDA5/CXCL10 axes in BMEC might play a role in the regulation of BBB functions, immune reactions and neuronal functions.…”
Section: Discussionmentioning
confidence: 99%